2020
DOI: 10.1111/1471-0528.16479
|View full text |Cite
|
Sign up to set email alerts
|

Association between chorionicity and preterm birth in twin pregnancies: a systematic review involving 29 864 twin pregnancies

Abstract: Background The perinatal mortality and morbidity among twins vary by chorionicity. Although it is considered that monochorionicity is associated with an increased risk of preterm birth in twin pregnancies, no systematic review exists evaluating this association. Objectives This systematic review was undertaken to assess the association between preterm birth and chorionicity in twin pregnancies. Search strategy We searched the electronic databases from January 1990 to July 2019 without language restrictions. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
2
16
0
1
Order By: Relevance
“…In our study, monochorionicity was significantly associated with preterm birth in twin pregnancy, which approximately doubled the risk for preterm birth in all gestations. The result was in accordance with a systematic review including 29,864 twin pregnancies published in 2020 (14). In this review, monochorionicity significantly increased the risk of preterm (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, monochorionicity was significantly associated with preterm birth in twin pregnancy, which approximately doubled the risk for preterm birth in all gestations. The result was in accordance with a systematic review including 29,864 twin pregnancies published in 2020 (14). In this review, monochorionicity significantly increased the risk of preterm (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 90%
“…Recommendations for early delivery for monochorionic twins may contribute to the increased preterm birth rate due to iatrogenic prematurity. However, a study also revealed that monochorionicity itself has a high association with spontaneous preterm birth (14). In our study, subgroup analysis was conducted to evaluate the effect of chorionicity on spontaneous and iatrogenic preterm birth before 32 and 34 weeks of gestation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The great variety in PTB rates signifies that there are epigenetic transgenerational stress factors and determinants from the social environment and the health care system 18 20 . In addition, perinatal morbidity and mortality among twins vary by chorionicity, and monochorionicity is significantly associated with an increased risk of PTB 21 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Previous studies have demonstrated the association between SPTB in twin pregnancies and speci c clinical indicators, such as ethnic origin, age, nulliparity, chorionicity, body mass index (BMI), tobacco usage, history of previous preterm delivery, cervical length and funnelling. [21][22][23][24][25][26][27][28][29][30][31][32] Different combinations of clinical variables might indicate different likelihoods of SPTB. The purpose of this study is to synthesize an array of maternal demographic factors and clinical variables and develop a practical algorithm to calculate the risk of SPTB for twin pregnancies, similar to the rst trimester genetic disease screening tools or the Framingham heart disease score.…”
Section: Introductionmentioning
confidence: 99%